Translating concurrent RSL into PVS - Dasso, Aristides (2003)
Translating RSL into PVS has been a way of obtaining a proof tool for RSL. However there are several styles or constructs of RSL that are harder to translate than others. One of them is concurrent RSL since PVS has no similar construct. We propose to study the problems involved in translating Concurrent RSL into PVS.